(3GdCSeGA GdNajI aj WHbGJ GdMfajIs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s; (3YHO GdbGOQ Hf eMeO Hf fUQGddg, GdeYQha HGHf CHj GdhaGA GdbQTj GdJejej GdeUQj,J (B775 (3g` s ((3GdMGL GdSjO eMeO HGQSG NhGLg GdHNGQi GdMfai GdfbTHfOi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdCQV hGdSeGA CeG HYO ajbhd GdhGKb HcQe QHg Efi deG hbafi Gddg SHMGfg HdWaI GdNai hJhajbI Gdhai Ydi cJGHI eSfO GdGeGe , TQM eSfO GdGeGe s
(3BNQgG (B:s
(3hcGf hGdOg ef GdYHGO GdePchQjf hGdRgGO hGdeTghQjf hcGf haGJg dHVY hSJeGFI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B42s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs